1976
DOI: 10.1007/bf00885657
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of clinical students on training in community mental health and community psychology

Abstract: Three hundred eighty-five advanced doctoral students from 102 training programs in clinical, clinical--community, and community psychology participated in as assessment of their training in community psychology/community mental health (CP/CMH). Significant findings included: (a) 66% consider training in CP/CMH as very helpful to their career goals, (b) 54% are very much interested in post-doctoral training in CP/CMH, and (c) 62% consider the training in CP/CMH available in their graduate programs below adequat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1978
1978
1994
1994

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…The survey included 36 items that addressed various topics of interest to community psychologists (according to Walfish et al, 1984; Andrulis et al, 1977; and Zolik, Sirbu, & Hopkinson, 1976), such as research methods, change and intervention procedures, and assessment procedures. All respondents were asked whether they had used each specific technique in either their field training or their graduate program (course work, supervision, etc.).…”
Section: Methodsmentioning
confidence: 99%
“…The survey included 36 items that addressed various topics of interest to community psychologists (according to Walfish et al, 1984; Andrulis et al, 1977; and Zolik, Sirbu, & Hopkinson, 1976), such as research methods, change and intervention procedures, and assessment procedures. All respondents were asked whether they had used each specific technique in either their field training or their graduate program (course work, supervision, etc.).…”
Section: Methodsmentioning
confidence: 99%
“…There do not appear to be more recent data regarding the CI training in Community Psychology training programs since surveys taken in the mid-1970s. At that time it ranked highly in polls concerning relevant courses by both students and faculty (Barton, Andrulis, Grove, & Aponte, 1976;Zolik, Sirbu, & Hopkinson, 1976). However only 55°7o of the students polled indicated that the academic coverage was adequate.…”
Section: Status Of Crisis Intervention (Ci)mentioning
confidence: 96%
“…Previous reports about the training of community psychology students have focused broadly on community-related training topics and processes (see Walfish, Polifka, & Stenmark, 1984;Zolik, Sirbu & Hopkinson, 1976). Only in a few cases, have community psychologists looked at training practices related to multicultural issues (Trickett, Irving, & Perl, 1984).…”
mentioning
confidence: 99%